Optimal Control for A SEIR Epidemiological Model Under the Effect of Different Incidence Rates - Derya Avcı (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
In this study, optimal control problem for a fractional SEIR epidemiological model under the effect of bilinear and saturate incidence rate functions is investigated. These rates play an important role in the realistic modeling of an epidemic by describing the interaction between susceptible and infected individuals of a population. This interaction is highly decisive in whether the disease will turn into a pandemic or not. Therefore, these functions can be defined in different forms depending on the course of the epidemic. The model discussed in this study is defined in terms of Caputo. Dimensional compatibility is guaranteed before posing the optimal control problem. The main objective of the proposed optimal control problem is to minimize the number of infected individuals and the cost of education given to susceptible individuals as a preventive measure. Euler-Lagrange equations corresponding to the optimality conditions of the considered model are first determined by Hamiltonian’s formalism. Afterward, the optimal system with right and left fractional Caputo derivatives are solved numerically by the forward-backward sweep method combined with the fractional Euler method. Optimal solutions are interpreted graphically for varying values of the incidence rate coefficients and the fractional parameter. According to the simulation results, it is seen that the education given to susceptible individuals is significantly effective in slowing down the epidemic.